Analysis of Factors Affecting the Participation of Women of Childbearing Age in Visual Inspection with Acetic Acid (VIA) in The Community Health Center of Bangkalan - Uswatun Khasanah; Siti Anisak; Nurlailis Saadah; Esyuananik Esyuananik; Anis Nurlaili (Journal of Global Pharma Technology, 2020)
Nurlailis Saadah1, Esyuananik1, Anis Nurlaili1 1Midwifery Department, Poltekkes Kemenkes Surabaya; Jl. Pucang Jajar Tengah 56 Surabaya (yusa_0510@yahoo.com) *Corresponding Author: Uswatun Khasanah Abstract Cervical cancer is a malignant disease that it is possible to cause death. Unfortunately, the community still has a very low awareness to check themselves.More than 70% of sufferers come to the hospital at an advanced stage that is difficult tocure. This study aims to analyze the factors that influence the participation of women of childbearing age in visual inspection using acetic acid in the community health center of Bangkalan. The study was conducted in March-June 2019 with a cross sectional study design. The number of research subjects was 104 women of childbearing age taken by cluster random sampling.The dependent variable included predisposing factors (knowledge, motivation, culture), supporting factors (distance to health facilities and income) and reinforcing factors (midwife counseling). The independent variable included the participation of women in childbearing age in the VIA test. Data analysis was performed using the chi square test and logistic regression with a significance level of α = 5%. The results showed that knowledge had an influence on the participation of women in childbearing age in VIA tests (p value 0.047 0.05).Knowledge is the initial factor of a behavior that is expected to be positively correlated with behavior. In addition, environmental influences (including culture) also shape the behavior. However,not all people are aware and ready to implement behavioral changes. The existence of socio-cultural influences with gender bias, as well as the lack of information and the ability to receive and absorb information can influence the norms and beliefs of the community in utilizing health services including the effort to take part in VIA tests. For this reason, it is necessary to conduct socialization to targets related to VIA inspection through printed and electronic media. In addition, health workers need to improve their skills in counseling based on VIA counseling standards. Keywords: Predisposing Factor, Reinforcing Factor, Enabling Factor, Women of Childbearing Age Participation, VIA Test